A Double-Edged Sword: Roles of Helicobacter Pylori in Gastric Carcinoma - Xue, Li-Jun; Su, Quan-Sheng; Mao, Xiao-Bei; Liu, Xiao-Bei; Lin, Qing; Liu, Chang; Lin, Yong; Yang, Ji-Hong; Yu, Hong-Ju; Chu, Xiao-Yuan (IntechOpen, 2011)
None